NANO₂ INTOKSIKATSIYASINING KALAMUSHLAR YURAGI VA ASOSIY GEMODINAMIK KO‘RSATKICHLARGA TA’SIRINI EKSPERIMENTAL BAHOLASH (Universal xalqaro ilmiy jurnal, 2026)
The aim of this study was to evaluate the changes in cardiac function and hemodynamicparameters in rats during 10-day exposure to Sodium nitrite. The study demonstrated that NaNO₂ exertsa toxicological effect on the organism, induces hypoxic conditions, and, through the production of nitricoxide (NO), causes relaxation of vascular smooth muscle, leading to vasodilation and a decrease inarterial blood pressure. In conclusion, a 10-day NaNO₂ intoxication results in disruption of thecardiovascular system in rats, manifested by a sharp decline in arterial blood pressure and an increasein heart rate. These findings confirm the development of hemodynamic disturbances due to the toxiceffect of nitrites.
Keywords: natriy nitrit; gipotenziya; vazodilatatsiya